Efficiency or Quality: The Continuing Relevance of H5P-Assisted Learning System in Indonesia’s Digital Talent Scholarship Program - Krismassion Prihationo; Munir; A. Sobandi; Budi Laksono Putro (Journal of Education Technology, 2025)
This study is motivated by the lack of comprehensive empirical evidence on the extent to which automation-based digital learning systems can enhance operational efficiency without compromising the quality of learners’ experiences in large-scale government training programs. This study aims to evaluate an H5P-assisted digital learning system implemented through the Microskill platform in the Digital Talent Scholarship Program. A descriptive quantitative approach was employed using data from 445,054 training participants and 44,794 post-training evaluation survey respondents. The results indicate a training completion rate of 63.7 percent, suggesting that learning process automation can reduce administrative workload through self-certification mechanisms and automated processing of learning activities without manual intervention. Pearson correlation analysis confirms positive relationships among all constructs, with the strongest associations observed between system quality and user satisfaction, as well as between user satisfaction and user loyalty. These findings demonstrate that automation enhances technical reliability while maintaining positive learning experiences through H5P-based interactivity. The practical implications of this study suggest that integrating automation with interactive instructional design can strengthen the efficiency, transparency, and instructional value of public digital training programs. These findings provide strategic insights for government training institutions in configuring automated digital learning systems without sacrificing instructional quality.